Return to sport after adolescent idiopathic scoliosis (AIS) correction surgery: a retrospective data analysis - Pepke, Wojciech; Madathinakam, Abhilash; Bruckner, Thomas; Renkawitz, Tobias; Hemmer, Stefan; Akbar, Michael (Journal of Clinical Medicine, 2023)
Sports are relevant to younger populations in society. Adolescent idiopathic scoliosis (AIS) patients who undergo surgical correction of the spine are often intensively involved in sports. For that, returning to the sport is often an important concern for the patients and their families. To the best of our knowledge, there is still a lack of scientific data indicating established recommendations about the time of returning to sport activities after surgical spinal correction. The aim of this study was to investigate (1) when AIS patients return to athletic activities after a posterior fusion, and (2) if they change their activities postoperatively. Furthermore, another question was (3) if the length of the performed posterior fusion or (4) fusion to the lower lumbar spine could have an influence on the rates or time of returning to sport activities postoperatively. Data collection was performed using questionnaires assessing patients’ contentment and athletic activity. Athletic activities were categorized into three categories: (1) contact, (2) contact/non-contact and (3) non-contact sports. The intensity of exercised sports, the time of returning to the sport and changes in sport habits were documented. Radiographs were evaluated pre- and postoperatively to determine the Cobb angle and the length of the posterior fusion via the identification of the upper (UIV) and lower instrumented vertebra (LIV). Stratification analysis due to the fusion length was performed to answer a hypothetical question. This retrospective survery of 113 AIS patients treated with a posterior fusion revealed that, on average, returning to sport activities required 8 months of postoperative rest. The preoperative to postoperative rate of patients participating in sport activities increased from 88 (78%) to 94 (89%). Furthermore, postoperatively, a relevant shift of exercised activities from contact to non-contact sports was noted. Further subanalysis revealed that only 33 subjects were able to return to exactly the same athletic activities as before surgery (10 months postoperatively). The assessment of radiographs revealed that in this study group, the length of the performed posterior fusion and fusions to the lower lumbar spine had no influence on the time of return to athletic activities. The results of this study might shed some light on postoperative recommendations for sport activities after AIS treatment with a posterior fusion and may be beneficial for surgeons treating patients.
Gesehen am 27.03.2023